Staff Training Needs For Dealing with Developing Communication Technologies - Ned Browning; Lenda Jo Anderson (Journal of Applied Communications, 1989)
Communication specialists within the USDA/land-grant educational system must be more than media producers. They must be educators, not necessarily of the general public, but of the personnel of the system for which they work. To be successful educators, they must know their subject, how to teach it, and what their students need to learn. For the communication specialist, a major challenge is to understand and train clients (subject matter specialists, field agents and administrators) for the Information Age. The study reported here suggests one way to gauge and evaluate needs for training in developing communication technologies by scrutinizing one client group. All of the nation's Extension clothing specialists were asked how they were using traditional and innovative media in their educational programs (Anderson & Browning, 1986). In the process, they prioritized their information technology training needs.